The Application of Well Injection Technology in the Produced Water Management Oil and Gas Industry - Sillak Hasiany (Penerbit Kemala Indonesia, 2020)
Produced water is the largest liquid waste generated from the production of oil and gas. The direct discharge of produced water into the environment can be harmful to human’s life and environmental. Thus, it needs to be managed, one of which is through the technology of well injection. Well injection technology is a technology where the produced water generated in the process of production of oil and gas will be returned to the earth by means of injecting it to injection wells. The purpose in this study was to identify the amount of produced water injected back into the injection wells and identify the constraints of the application of well injection technology in the company. The primary and secondary data were collected through field observations, laboratory analysis, and interviews. Descriptive analysis was conducted to know the constraints and benefits of applying this technology. The results showed that the re-injection technology was able to inject produced water of 37158 barrels per day. However, this technology led the wells to be increasingly saturated and leakage to produced water re-injection pipes